ESTIMASI PENGARUH INFLASI DAN TINGKAT OUTPUT TERHADAP RETURN DAN VOLATILITAS SAHAM DI INDONESIA (PENDEKATAN MODEL GARCH, TARCH DAN EGARCH) - Rahayu, Dyah Sih; Firmansyah, Firmansyah (JURNAL BISNIS STRATEGI, 2005)
This study examines whether movement in two key macroeconomic variables - level output and inflation - in Indonesia influence the monthly stock returns and volatility.By mainly applying GARCH, TARCH and EGARCH models, this study has demonstrated that time varying and the leverage effect appears to exist in Indonesia's stock returns volatility. At any models, inflation and output level have no effect on stock returns. The result for the variance equation show that only the inflation has significance effect on stock returns volatility.